Proposed Strategy Marketing For Kids Footwear Product ( Case Study: The Little Harper) (The Indonesian Journal of Business Administration, 2014)
Abstract. Nowadays many mothers dress up their kids, then get picture of them through their handphone or tablet, and then they upload that photo to social media like Facebook, Twitter, or Instagram. The Little Harper attempted to capture that phenomena for their business. That is why they are selling their product online through social media. It is not easy to do online business, especially new online shop. The Little Harper had to face problem, such as lack of brand awareness, lack of trust from their customers, and compete with other online shop. A survey have been conducted to mothers who had child between 0-5 years. Purpose of this survey to know opinion and habit of them when buying their child shoes. A statistical analysis is used to help finding best solution for solving The Little Harper’s problem. First, cluster analysis is used to classify 102 individuals into 3 clusters based on 29 variables. Second, cross tabulation analysis is used to know which cluster has most respondent according to age, level of education, occupation, and monthly expenditure. According to cross tabulation analysis result, cluster 1 is selected clusters among 3 clusters. The last step, discriminant analysis is used to choose variables that have influence in intensity purchases of The Little Harper’s customers. Result from discriminant analysis will be target of The Little Harper to attract their target market. Besides that, customer profiles of target market also be required by The Little Harper. This customer profiles is just from cluster 1 as selected cluster. After that, positioning formula must be created to makes The Little Harper’s brand look different with others and has certain image in their customer’s mind. For increasing trust from customers, The Little Harper will make return facility and payment method through transfer between bank account. For increasing brand awareness, The Little Harper will use celebrity endorsement, do sales promotion, and put advertisement in print media. Key Words: marketing strategy, cluster analysis, discriminant analysis, kids footwear, kids shoes